Characteristics and Risk Factors of Helicobacter pylori Associated Gastritis: A Prospective Cross-Sectional Study in Northeast Thailand. (2nd March 2016) - Tongtawee, Taweesak; Kaewpitoon, Soraya; Kaewpitoon, Natthawut; Dechsukhum, Chavaboon; Leeanansaksiri, Wilairat; Loyd, Ryan A.; Matrakool, Likit; Panpimanmas, Sukij
Abstract : Background and Aim . Risk factors for Helicobacter pylori infection are genetic susceptibility and poor living conditions. This study aimed to investigate the Mdm2 gene, clarithromycin resistance, and possible risk factors for Helicobacter pylori infection. Methods . Risk factors and clinical characteristics were analyzed, including patient demographic data, patient income, personal history, possible source of transmission, patient symptoms, endoscopic findings, patterns of clarithromycin resistance, and patterns of Mdm2 SNIP309. Results . Ingestion of pickled fish (OR = 11.27, 95% CI = 4.31–29.45, p < 0.0001 ), salt crab (OR = 8.83, 95% CI = 1.99–39.14, p < 0.001 ), and Papaya salad (OR = 8.73, 95% CI = 4.54–16.79, p < 0.01 ). The prevalence of clarithromycin resistance was 56% (wild type, A2143/2142A, is 23.8%; mutation, A2143/2142CG, is 35.7%; wild type + mutation is 40.5%). The genetic polymorphisms of Mdm2 SNIP309 were SNIP309 T/T homozygous in 78%, SNIP309 G/T heterozygous in 19%, and SNIP309 G/G homozygous in 3%. Conclusion . Pickled fish, salt crab, and Papaya salad are positive risk factors. There was high prevalence of clarithromycin resistance. The Mdm2 SNIP309 G/G homozygous genotype might be a risk factor for gastric cancer and the fact that it is infrequent in Thailand.